SIFT approach to blood vessel matching - Tan, Ke Bin. (2010)
This report describes the author’s experience and progression in his final year project, titled, “SIFT Approach to Blood Vessel Matching”. During the project, the author learnt to apply the Scale-Invariant Feature Transform (SIFT) method to match pictures of blood vessels.